Menggagas Tafsir Ayat Hukum Dalam Kerangka Fiqh Al-Ikhtilaf - Jabbar Sabil (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2016)
Opinion differences in the interpretation of verses regarding jurisprudence might create an impression that there is a disharmony among the teachings of the Qur'an. In fact, verse 82 of Surah An-Nisa emphasize that there is no contradiction in the Qur'an. However, jurisprudence studies do not accommodate this issue. The differences are perceived only as problems of furukiyah. This difference indeed emerges on the fundamental issues of Islamic teaching. Unfortunately, interpretation studies do not address this issue either as its orientation focuses more on the discovery of meaning. Therefore, this paper offers a theoretical framework of fiqh al-ikhtilaf in order for the interpretation not to see differences in jurisprudence verses as a contradiction but see it as a form of diversities (al-ta'addud al-tanawwu'). By combining deductive interpretation and critical analysis method, this paper studies the philosophical basis in the interpretation of jurisprudence verses. The philosophical foundations include basic assumptions, paradigms, and theoretical framework. Furthermore, using a philosophical approach, this study concludes that the theoretical framework of fiqh al-iktilaf is appropriate to address the differences in the interpretation of the jurisprudence verses.